Prospects for the Implementation of High-Speed Railway in Ukraine - Kurhan, M. B.; Kurhan, D. M.; Khmelevska, N. P.; Kovalskyi, D. L. (Science and Transport Progress, 2025)
Purpose. The European Union has an ambitious goal of significantly expanding the network of high-speed railway lines. Currently, Ukraine lacks direct experience in constructing high-speed railways compared to European projects. Despite this, Ukraine has a strategy for developing high-speed rail connections. This study aims to analyze and justify the conditions under which the construction of the Kyiv–Lviv–Warsaw high-speed rail corridor can become an economically viable project, bringing significant economic, social, and environmental benefits. Methodology. To assess the feasibility of constructing a high-speed railway along a new route, the authors applied a forecasting and efficiency evaluation model for railway transportation, considering all costs using the NPV (Net Present Value of Discounted Cash Flow) indicator. NPV serves as a powerful tool for investment project evaluation, allowing for informed financial decision-making by considering the time value of money and maximizing investment profitability. Findings. The study identifies the conditions under which the construction of the Kyiv–Lviv–Warsaw high-speed rail corridor can become an economically viable project. As passenger train volumes increase, the net discounted revenue grows linearly, with its magnitude depending on the construction costs of the high-speed railway. To enhance project profitability, it is more critical to focus on increasing transportation volumes rather than reducing construction costs. Originality. The new findings are based on the application of scientific approaches such as a comprehensive and detailed study of various aspects of high-speed railway design in Europe. This has enabled the improvement of the interoperability between Ukrainian and European transport systems and provided recommendations for organizing high-speed rail services in Ukraine. Practical value. Based on the obtained results, further development of railway infrastructure along high-speed rail corridors is possible through innovative advancements and the enhancement of scientific and technological potential. Addressing issues related to the implementation of analysis and evaluation methods for selecting high-speed rail options serves as the foundation for the planning and construction of high-speed railway routes in Ukraine.